2020
DOI: 10.1186/s12864-020-07110-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptomic analysis provides new insights into the mechanism of ray floret morphogenesis in chrysanthemum

Abstract: Background The ray floret shapes referred to as petal types on the chrysanthemum (Chrysanthemum × morifolium Ramat.) capitulum is extremely abundant, which is one of the most important ornamental traits of chrysanthemum. However, the regulatory mechanisms of different ray floret shapes are still unknown. C. vestitum is a major origin species of cultivated chrysanthemum and has flat, spoon, and tubular type of ray florets which are the three basic petal types of chrysanthemum. Therefore, it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Moreover, recent data collected in Chrysanthemum × morifolium Ramat. showed that the involvement of a different set of hormone‐related genes can be identified between ray and disk flowers (Pu et al, 2020). Overall, these data would indicate that in Asteraceae a complex regulatory network controls the different forms of inflorescences.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent data collected in Chrysanthemum × morifolium Ramat. showed that the involvement of a different set of hormone‐related genes can be identified between ray and disk flowers (Pu et al, 2020). Overall, these data would indicate that in Asteraceae a complex regulatory network controls the different forms of inflorescences.…”
Section: Resultsmentioning
confidence: 99%
“…To decide on pappus–sepal homology, we first observed the floral development of dandelion micromorphologically ( Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 ; Supplementary Figures S1–S5 and Video’s SV1 and SV2 ) and defined the different stages of floral initiation, floral maturation, and seed formation ( Table 1 ). Well-defined stages of floral ontogenesis are available for some model species, particularly Arabidopsis [ 63 ], but in the Asteraceae the main focus has been on the inflorescence and not florets development, for instance in Gerbera [ 64 ], with additional floral initiation stages in [ 65 ], and recent studies in Chrysanthemum [ 66 ], lettuce [ 53 ], and the rubber dandelion ( T. kok-saghyz ) [ 67 ]. Our study concerns the floret development only, starting with the floral primordium as stage 1 , and is aimed as a reference for dandelions and, where possible, other Asteraceae.…”
Section: Discussionmentioning
confidence: 99%
“…In this work (Fig. 9 ), ERF, Trihelix, WRKY and C3H family members were identified in chrysanthemum, and were upregulated during chrysanthemum flower bud differentiation or development [ 35 41 ]. This implies that these genes may be involved in flower developmental processes, and these TFs should be further studied in chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%
“…Flower bud differentiation or development are important tissue to chrysanthemum for tea. Flowering is a complex process controlled by gene expression and phytohormones [33][34][35][36][37][38][39][40]. In chrysanthemum, important transcription factors (TFs) involved in flower development have been isolated and analyzed, including those encoded by the homologs of the Arabidopsis genes APETALA1, SEPALLATA3, FRUITFULL, LEAFY, APETALA2,TEOSINTE BRANCHED1/ CYCLOIDEA/PROLIFERATING CELL FACTOR20, and CYCLOIDEA2c, as well as many genes encoding MADSbox and WUSCHEL (WUS)-like proteins [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%